Integrasi Kerentanan Fisik Pesisir Berbasis Coastal Vulnerability Index (CVI) dalam Evaluasi Arahan Pemanfaatan Ruang RTRW - Abudzar Algiffari (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
Coastal areas are highly dynamic and increasingly exposed to physical pressures such as coastal erosion, shoreline change, inundation, and sea-level rise. In Indonesia, most coastal vulnerability studies remain focused on physical mapping and have not been systematically integrated with spatial planning evaluation. This study aims to analyze physical coastal vulnerability using the Coastal Vulnerability Index (CVI) and integrate the results with the Regional Spatial Plan (RTRW) in the coastal areas of Mangarabombang and Laikang Sub-districts, Takalar Regency. A quantitative spatial approach was applied using eight parameters, which were reclassified into vulnerability scores, transformed into CVI values, and classified using quartile methods. The results show that high and very high vulnerability classes dominate the coastal area. Spatial integration reveals that several development zones intersect with high vulnerability levels, indicating potential spatial mismatch. This study confirms that CVI can be operationalized as a spatial evaluation tool to support adaptive and risk-based coastal planning.